Flow cytometric characterisation of the complex polyploid genome of Saccharum officinarum and modern sugarcane cultivars - Metcalfe, Cushla J; Li, Jingchuan; Giorgi, Debora; Doležel, Jaroslav; Piperidis, Nathalie; Aitken, Karen S (Scientific reports, 2019)
Sugarcane (Saccharum spp.) is a globally important crop for sugar and bioenergy production. Its highly polyploid, complex genome has hindered progress in understanding its molecular structure. Flow cytometric sorting and analysis has been used in other important crops with large genomes to dissect the genome into component chromosomes. Here we present for the first time a method to prepare suspensions of intact sugarcane chromosomes for flow cytometric analysis and sorting. Flow karyotypes were generated for two S. officinarum and three hybrid cultivars. Five main peaks were identified and each genotype had a distinct flow karyotype profile. The flow karyotypes of S. officinarum were sharper and with more discrete peaks than the hybrids, this difference is probably due to the double genome structure of the hybrids. Simple Sequence Repeat (SSR) markers were used to determine that at least one allelic copy of each of the 10 basic chromosomes could be found in each peak for every genotype, except R570, suggesting that the peaks may represent ancestral Saccharum sub genomes. The ability to flow sort Saccharum chromosomes will allow us to isolate and analyse chromosomes of interest and further examine the structure and evolution of the sugarcane genome.
Keywords: alely; karyotyp; DNA, Plant; Chromosomes, Plant; Cell Cycle; Alleles; hydroxymočovina; Fluorescence; Genome, Plant; Hydroxyurea; Kinetics; kořeny rostlin; Karyotype; Flow Cytometry; DNA rostlinná; průtoková cytometrie; fluorescence; Saccharum; chromozomy rostlin; Plant Roots; polyploidie; Polyploidy; genom rostlinný; buněčný cyklus; kinetika